Evaluation of noise environments during daily activities of university students. Issue 2 (2nd April 2016) - Tristán Hernández, Edgar; Pavón García, Ignacio; López Navarro, Juan Manuel; Kolosovas-Machuca, Eleazar Samuel
Abstract : Noise conditions specifically in areas inside university facilities and its impact on the quality of life of university students are topics that have received little attention. This paper presents a study of the noise conditions in which university students of various institutions in Madrid, Spain, carry out their daily studies. A representative number of measurements was carried out using noise dosemeters and dataloggers in order to evaluate the levels of noise, noise dose and exposure to noise during school periods and extracurricular activities. The results were compared with the recommendations given by current environmental noise regulations. This paper was complemented with a survey to get to know how students perceive the exposure to noise in university environments.